P05.09 Phenotypic, genetic and genomic characterisation of the 2015 who neisseria gonorrhoeae reference strains for quality assurance of laboratory investigations globally. (13th September 2015) - Unemo, M; Golparian, D; Grad, Y; Limnios, A; Wi, T; Lahra, M; Harris, S
Abstract : Introduction: Gonorrhoea and antimicrobial resistance (AMR) in Neisseria gonorrhoeae are major public health concerns globally. Resistance to all antimicrobials available for treatment of gonorrhoea has now been reported in N. gonorrhoeae . Enhanced quality assured gonococcal AMR surveillance is crucial worldwide and the WHO Global Gonococcal Antimicrobial Surveillance Programme (GASP) was revitalised in 2009. To obtain reliable and comparable AMR data internationally, appropriate and well-characterised N. gonorrhoeae reference strains are essential for quality assurance. The phenotypic and genetic characteristics of the 2008 WHO N. gonorrhoeae reference strains (n = 8) were previously published. Here, we describe the phenotypic, genetic, and genomic characteristics of the 2015 WHO N. gonorrhoeae reference strains. Methods: In the 2015 WHO N. gonorrhoeae reference strain panel (n = 14), six additional strains have been selected to include representation of high-level cephalosporin and azithromycin resistance and porA mutant strain. These strains were phenotypically characterised by antibiogram, serovar, and prolyliminopeptidase (PIP) screening; and genetically in regards of resistance plasmid types, polymorphisms in divergent genetic resistance-mediating loci (n = 14), porB sequencing, N. gonorrhoeae multiantigen sequence typing (NG-MAST), and multi-locus sequence typing (MLST). Fully characterised finished reference genomes for all the 2015 WHO N. gonorrhoeae reference strains were produced using PacBio and Illumina sequencing technologies. Results: The 2015 WHO reference strains represent all available main phenotypes of resistance and susceptibility to antimicrobials previously and currently used for treatment of gonorrhoea, as well as several considered for future use. All corresponding resistance genotypes and molecular epidemiological types were also elucidated. Finally, references genomes of each strain were obtained and characterised in detail. Conclusion: The 2015 WHO N. gonorrhoeae reference strains are intended for internal and external quality assurance in all types of laboratory investigations, i.e. particularly in GASP, but also for phenotypic (e.g. culture) and molecular diagnostics, species determination, genetic AMR detection, molecular epidemiology, and genome sequencing as well as other novel molecular technologies. Disclosure of interest statement: This work was funded by the Örebro County Council Research Committee and the Foundation for Medical Research at Örebro University Hospital, Sweden, the WHO, and The Wellcome Trust Sanger Institute, Wellcome Trust Genome Campus, Cambridgeshire, United Kingdom.